Ashitaba's instant chemical and sensory qualities (Angelica Keiskei) - Istiqamah, Nur Annisa; Ihromi, Syirril (Universitas Muhammadiyah Mataram, 2024)
Ashitaba (Angelica keiskei) is one of the introduced plants originating from Japan,precisely from the island of Hanchijojima which is not widely known in Indonesia. This plantis rich in beta-carotene, vitamins B1, B2, B3, B5, B6, B12, biotin, folic acid and vitamin C,and also contains several minerals such as calcium, magnesium, potassium, phosphorus,zinc and copper. can grow well on Mount Rinjani, East Lombok, West Nusa TenggaraProvince, which is located in Sembalum Village. This plant has potential as a medicinebecause the yellow sap contains chalcones such as xanthoangelols (Xas), 4-hydroxyderricin (4-HD) and isobavachalcone. The active substance contained inchalcone is useful for maintaining glucose homeostasis, increasing red blood cellproduction, increasing concentration power. Based on the description above, thisresearch raises the topic of making Ashitaba leaves into instant drinks in various typesand concentrations of sugar. The types of sugar used are brown sugar and granulatedsugar with concentrations of 20%, 30%, 40%, 50%, 60%. carried out several tests of thecontent of instant ashitaba powder, namely testing water content, reducing sugarcontent and organoleptic tests for color, aroma, taste and texture. Data analysis wasperformed using a completely randomized design (CRD) with two factors, consisting oftypes of sugar (brown sugar and granulated sugar). From the test results, it was foundthat the lowest water content of 2.76% was found in the treatment of granulated sugarwith a concentration of 60% (G1W5), Reducing sugar levels showed that the treatmentof granulated sugar with a concentration of 20% (G1W1) had the highest levels of 8.33%and 3.61 mg. In organoleptic testing (color, taste, aroma and texture) the results showedthat the treatment using granulated sugar with a concentration of 60% (G1W5) had thequality of color, taste, aroma and texture favored by the panelists.